Pityriasis rubra pilaris treatment options: A retrospective case series from a tertiary hospital. Issue 6 (20th September 2021) - Ringin, Sarah; Baker, Christopher S.; Foley, Peter; Daniel, Benjamin S.
Abstract: Pityriasis rubra pilaris (PRP) is a group of uncommon chronic inflammatory skin conditions with unclear pathophysiology and etiology. To date there is limited published literature and no clinical guidelines for the management of PRP. Infliximab, alone or in combination, is the most widely published successful treatment for adults and etanercept for pediatric populations. We present a case series of patients diagnosed with PRP. Retrospective data were collected from a tertiary Australian dermatology department between January 2010 and December 2019 on patients with PRP. Electronic medical records and pathology database were searched. A total of 13 patients were included. Twelve of the 13 patients used topical agents and three patients attempted narrow‐band ultraviolet B phototherapy. All patients received acitretin as first line systemic agent with the dose varying from 10 to 50 mg daily. Six patients treated with acitretin reported adverse events, requiring dose reduction or cessation. Of the nine patients who did not receive a biologic agent, complete clearance of PRP was achieved in five cases. At least one biologic agent was used in four cases with two experiencing a marked improvement. Overall, complete clearance was achieved in six patients. PRP continues to be a challenge to treat with many treatment options used with variable efficacy.